Effect Of SiC/Fly Ash Reinforcement On Surface Properties Of Aluminum 7075 Hybrid Composites - Pedapati, Srinivasa Rao; Patil, Namdev Ashok; Mamat, Othman; Lubis, Abdul Munir Hidayat Syah (MDPI AG, 2020)
Friction stir processing (FSP) has emerged as a valuable technique in the surface metal matrix composite fabrication field. In this process, solid-state processing mostly avoids the formation of detrimental phases inside composites. Despite having a high specific strength, further extensive Al alloy applications are limited due to their poor surface properties. A hybrid reinforcement approach can be used to improve surface properties. In this study, industrial waste fly ash material is mixed with hard SiC ceramic particles. The main focus of this research is to improve wear resistance under dry sliding conditions and microhardness of aluminum 7075-T651 by dispersion of silicon carbide-fly ash (SiC/fly ash) powder in a base alloy by FSP. The parameters used for this investigation are: tool rotation rpm (500, 1000 and 1500), the tool traverse mm/min (20, 30 and 40), the reinforcement's hybrid ratio HR (60:40, 75:25 and 90:10) and the volume percentage vol.% (4%, 8% and 12%). The influence of these parameters on the resultant composite's microstructure, dry sliding wear rate and micro-hardness was studied. By using response surface methodology (RSM), desirable ranges of process parameters for lower wear rate and higher microhardness were obtained. The interaction effect of SiC/fly ash volume percentage and hybrid ratio had the most influential effect on the wear rates, as well as microhardness of composites. Moreover, microhardness increased with an increase in the volume percentage of SiC/fly ash powders towards high SiC content in hybrid ratio. Interestingly, among stirring parameters, tool traverse speed was found to be more influential than tool rotational speed. The minimum wear rate was observed for the Run 20 sample (w: 1000 rpm, v: 40 mm/min, HR: 75:25, vol.%: 8). A maximum microhardness of 241.20 HV was achieved for Run 15 (w: 500 rpm, v: 40 mm/min, HR: 90:10, vol.%: 12) sample. Mainly, reinforcement distribution-in accordance with the stirring action generated by the tool-had a major role in controlling the surface properties of the resultant composites.